PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS DISCOVERY MATERI SISTEM PENCERNAAN MANUSIA UNTUK SISWA SMAS KAMPUS TELUKDALAM TAHUN PEMBELAJARAN 2021/2022 - Iman Mardiana Bohalima (Universitas Nias Raya, 2022)
Learning resources are anything that can be used to support and facilitate the learning process. Learning resources consist of teaching materials that have been prepared by educators with the aim to provide to students by supporting the learning process of students. This study aims to produce interactive learning media products on the human digestive system material that is valid, practical and effective. This type is the development of the PLOMP model. The research method used in this study is research and Development. The results of the research that researchers get through that has been distributed is a questionnaire which states that the Interactive Learning media tested is very valid, practical, and very effective. Student motivation is categorized as very high. As well as student learning outcomes in the Cognitive Realm stated excellent results. So through these results it is concluded that the development of interactive learning media on the material of the human digestive system is valid, practical and effective, to support student learning outcomes. Researcher suggestions are (1) biology subject teachers should be able to use learning modules as teaching materials in the learning process because it can increase students ' interest and motivation to learn (2) through this teaching material hopefully students can broaden their horizons about learning biology in the human digestive system material (3) for further researchers, Interactive Learning media in the human digestive system material can be used as reference material in relevant research.